Polyorchidism: a torted right-sided supernumerary testis - Thyoka, Mandela (BMJ Publishing Group, 2013)
Polyorchidism is a rare congenital anomaly defined by the presence of more than two histologically proven testes. The commonest variant is triorchidism, the supernumerary testis being commonly reported on the left side. Most cases of polyorchidism are found incidentally in association with undescended testis, hydrocele, hernia or torsion. We report a right-sided triorchidism in a 15-year-old boy found at time of groin exploration for an irreducible right inguinal hernia.